Enhancing Competitive Advantage in the Travel Industry: A Strategic Analysis of Creart Travel - Salsabila, Nabila; Mirzanti , Raafaldini (Syntax Corporation, 2025)
The travel industry contributes to total global revenue showcasing its significant contribution to the global economy in 2019-2024. This revenue includes earnings from services such as flights, accommodations, tours, transportation, and other travel related activities. The travel industry employs 3 million people, demonstrating its role as a major employment generator. Emerging as a significant entity within Indonesia's tourism industry, Creart Travel as part of PT. Semesta Muda Berkarya, providing a range of cutting-edge travel services suited to both individual and business customers. Despite its tremendous potential, the company faces obstacles including low brand awareness, fierce competition in the industry, and a slow rate of growth. This research will examine Creart Travel's present business strategy and pinpoint workable alternatives in order to strengthen the company's competitive edge and accomplish sustainable development. Both internal and external analyses are part of the comprehensive research technique used in this study. Instruments consisting of Porter's Five Forces framework, the Internal-External (IE) Matrix, and SWOT analysis are used to evaluate the company's internal strengths and weaknesses, in addition to its external opportunities and threats it confronts. Primary data gathered from corporate clients, when combined with secondary data derived from industry studies, provides important insights into market trends, customer needs, and competition strategies. According to the findings, Creart Travel's essential strengths derive from its strategic connections, customer-oriented service offerings, and creative travel packages. Nonetheless, limited brand visibility and a lack of individuality in marketing methods hinder its development. The study advocates for the implementation of targeted strategies, including the enhancement of digital marketing campaigns, the exploration of niche markets such as bleisure (business-leisure) travel, and the augmentation of service personalization, in order to attract and retain clientele.